Ratiometric luminescence behavior of lanthanide-mixed benzenedicarboxylates frameworks - Kitt Panyarat (2018)
© 2017 Elsevier B.V. The isostructural [Ln(L)0.5(NO2-BDC)(H2O)]·3H2O complexes (Ln = EuIII(I), TbIII(II), GdIII(III) and 0.012EuIII/0.494TbIII/0.494GdIII(IV); L = BDC2−or BDC2−/NO2-BDC2−; H2BDC = 1,4-benzenedicarboxylic acid) were synthesized and characterized by powder X-ray diffraction and wavelength dispersive X-ray fluorescence. Room temperature and temperature dependent photoluminescence behavior of the title complexes were studied in solid state using the ground crystals. The rare constant intensity of EuIIIwith increasing temperatures in complex I is reported, and a potential of the mixed complex IV as a ratiometric luminescence thermometer in a temperature range 333(2)–423(2) K is illustrated.